Mechanisms for Improving the Integration of Higher Education and General Secondary Education - Gadoymurodovna, Saidova Zilola (International Journal on Integrated Education, 2023)
In this article, the topic of interdisciplinary communication integration is researched in the era of highly accelerated scientific development. Also, the integrated improved mechanisms of the modern educational process are studied in the article. It has been analyzed that this is an unrepeatable stage for modern higher and general secondary education.